On a collection of fish from Manjaly - an estuarine area of the river Periyar in Ernakulam district, Kerala, India - Shyla, M. H.; Jameela Beevi, K. S. (Journal of the Bombay Natural History Society (JBNHS), 2014)
No Abstract.